2014
DOI: 10.1016/j.bbamcr.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cellular Ca2+ availability enhances TDP-43 cleavage by apoptotic caspases

Abstract: Accumulation of transactive response DNA binding protein (TDP-43) fragments in motor neurons is a post mortem hallmark of different neurodegenerative diseases. TDP-43 fragments are the products of the apoptotic caspases-3 and -7. Either excessive or insufficient cellular Ca(2+) availability is associated with activation of apoptotic caspases. However, as far as we know, it is not described whether activation of caspases, due to restricted intracellular Ca(2+), affects TDP-43 cleavage. Here we show that in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…In vitro experiments revealed that multiple caspases (caspases-3, -4, -7 and -9) cleave TDP-43 in cultured cells [ 6 , 11 , 26 , 29 , 42 ]. However, these in vitro experiments introduced caspases by transfection into cultured cells and did not tell us whether some of these caspases can endogenously determine the specific cleavage of TDP-43 in the primate brains.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments revealed that multiple caspases (caspases-3, -4, -7 and -9) cleave TDP-43 in cultured cells [ 6 , 11 , 26 , 29 , 42 ]. However, these in vitro experiments introduced caspases by transfection into cultured cells and did not tell us whether some of these caspases can endogenously determine the specific cleavage of TDP-43 in the primate brains.…”
Section: Resultsmentioning
confidence: 99%
“…The exact functions of these truncated species remain unclear and are generally thought to be toxic, but have also been proposed to serve a protective role in the cell to promote TDP-43 clearance [59,63,73,[75][76][77][78][79][80]. It is important to recognize that other species of TDP-43 CTFs have been identified at 15-16 kDa, 22-25 kDa, and 33-37 kDa in ALS/ALS-FTLD, however due to low levels of reporting their prevalence in disease remains elusive [56,74,75,[81][82][83][84][85].…”
Section: Main Textmentioning
confidence: 99%
“…Although the associated N-terminal fragments (NTFs) of TDP-43 are degraded quickly, the CTFs form aggregates that can also contain fulllength TDP-43. CTF35 is generated by caspase-3/7-mediated cleavage after Asp89, which is embedded in the consensus caspase-recognition motif [13][14][15][16] . Initially, Asp219 was suggested as the candidate cleavage site for CTF25; however, the estimated molecular weight of the fragment that comprises a.a. 220-414 is less than 25 kDa (refs 13,16,17).…”
mentioning
confidence: 99%